To live with(out) violence a second look 2--excerpts : final report violence against women Zenica, Bosnia-Herzegovina - Peele, Holly; Andric-Ruzicic, Duska; Medica Infoteka (Zenica Medica Infoteka, 1999)
Excerpts from the original book written in the Bosnian language by Medica professionals working in the Women's Therapy Center. These professionals relate their experiences in working with these women survivors of violence
Includes bibliographical references (p. 93-94).
UCWS-3039g donated by Edna Aquino
Keywords: Women -- Violence against -- Bosnia and Herzegovina -- Zenica; Abused women -- Bosnia and Herzegovina -- Zenica